Wheat bran feruloyl oligosaccharides ameliorate AAPH-induced oxidative stress in HepG2 cells via Nrf2 signalling. (August 2016) - Zhang, Huijuan; Wang, Jing; Liu, Yingli; Gong, Lingxiao; Sun, Baoguo
Highlights: Wheat bran feruloyl oligosaccharides (FOs) had protective effects against AAPH-induced oxidative stress in HepG2 cells. FOs increased the activities and mRNA expression levels of phase II detoxifying/antioxidant enzymes, such as SOD, CAT, and GPx. FOs simultaneously increased the protein expression levels of SOD, CAT, GPx, and Nrf2. Abstract: Protective effects of wheat bran feruloyl oligosaccharides (FOs) against 2, 2′-Azobis (2-methylpropionamidine) dihydrochloride (AAPH)-induced oxidative stress in HepG2 cells were investigated. The cytoprotective effects of FOs against oxidative challenge were determined by cell viability, intracellular reactive oxygen species (ROS) generation, and lactate dehydrogenase (LDH) leakage. The antioxidant activities of FOs were investigated by determining the activities and mRNA expression levels of phase II detoxifying/antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). FOs concentrations had a positive correlation with cell viability and a negative correlation with the LDH activity. FOs treatment increased the activities and mRNA levels of SOD, CAT, and GPx. Moreover, the nuclear factor E2 related factor (Nrf2) protein expression in the FOs group positively correlated with the SOD, CAT, and GPx protein levels. Thus the results demonstrated that FOs treatment could ameliorate AAPH-induced oxidative stress in HepG2 cells via Nrf2 signalling.